Climatological characteristics of cloud-to-ground lightning activity in the contiguous United States - Zajac, Bard A., author; Rutledge, Steven A., author (Colorado State University. Libraries, 1998)
We present a national climatology of cloud-to-ground (CG) lightning in the contiguous United States from 1995-97 using data from the National Lightning Detection Network. Annual statistics, cumulative frequency distributions, and annual and daily variations are documented with a series of maps with 100 km spatial resolution. We also identify characteristics of convective events which produced positive CG lightning over two case study areas located in the north-central U.S. and along the Gulf coast. Characteristics of convective events were identified by comparing plots of CG strike locations with national radar summaries. Surface features such as elevated and depressed terrain, coastlines, and the Gulf Stream appear to control the location, magnitude, daily frequency, and timing of CG lightning activity. Cumulative frequency distributions of daily CG flash count show a similar degree of skewness throughout the contiguous U.S. The majority of cloud-to-ground lightning is produced during summer over all areas in the contiguous U.S. with the exception of the south-central U.S. and the Pacific Coast. Summertime CG lightning activity over the western and eastern U.S. exhibits a diurnal cycle with a well-defined time of maximum frequency occurring in the afternoon or early evening. Over the central U.S. summertime CG lightning activity is complex with significant longitudinal variations in daily activity. The production of positive cloud-to-ground lightning over the north-central U.S. is dominated by convective events which occur during summer and during the late afternoon and evening hours. These events comprise thunderstorms, some of which produce predominantly positive CG lightning and are likely severe. Over the Gulf coast, positive CG lightning is produced throughout the year, by diurnally-forced convection during the warm season and by mesoscale convective systems with a really-extensive stratiform regions during the cold season.
April 1998.
Based on Bard A. Zajac's thesis (M.S.) -- Colorado State University, 1998.
Keywords: Lightning -- United States; Convection (Meteorology)